2017
DOI: 10.1097/bot.0000000000000911
|View full text |Cite
|
Sign up to set email alerts
|

Primary Posterior Blade Plate Tibiotalar Arthrodesis: A Salvage Procedure for Complex Nonreconstructable Pilon Fractures

Abstract: A subset of C2/C3 pilon fractures, open pilon injuries, metaphyseal bone comminution, and those involving substantial soft tissue or vascular injury may be nonreconstructable. Such injuries are at risk of progress to nonunion and failing open reduction internal fixation (ORIF). The risk of infection, malunion, and nonunion is relatively high with such injury patterns. In such cases, tibiotalar arthrodesis is performed after ORIF fails as a salvage procedure. Overall, the literature agrees that all pilon fractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Posterior and lateral plate fixation have been developed to avoid the high rate of wound complications and hardware irritation associated with anterior arthrodesis. 14-17 It should be noted that lateral and posterior plate fixation are also reasonable options for tibiotalar arthrodesis.…”
Section: Discussionmentioning
confidence: 99%
“…Posterior and lateral plate fixation have been developed to avoid the high rate of wound complications and hardware irritation associated with anterior arthrodesis. 14-17 It should be noted that lateral and posterior plate fixation are also reasonable options for tibiotalar arthrodesis.…”
Section: Discussionmentioning
confidence: 99%
“…That has led some physicians to advocate for primary arthrodesis in some of those patients. 14,15,17 Ideally, that treatment should be reserved for a select cohort of patients who are at increased risk for complications after ORIF. However, very little has been done to define those factors associated with arthrodesis following operative fixation of pilon fractures.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, preserving ankle joint function was challenging given the large bone defect and the absence of almost half of the cartilage on the joint surface. Some recent studies have reported that primary arthrodesis has resulted in good functional outcomes [[7], [8], [9], [10]]. The patient was made aware of this fact and that primary arthrodesis was one treatment option that would allow for his early reintegration into society.…”
Section: Discussionmentioning
confidence: 99%